A fault tolerant CSA in QCA technology for IoT devices - Saeid Seyedi; Hatam Abdoli (Scientific Reports)
Abstract According to recent research, with the ever-increasing use of Internet of Things (IoT) devices, there has arisen an ever-growing need for high-performance yet low-power circuits that can efficiently process information. Quantum-dot Cellular Automata (QCA) has emerged as a promising alternative to conventional complementary metal-oxide-semiconductor (CMOS) technology due to its great potential in digital design at nanoscale levels on account of very low power consumption and very high processing speed. However, QCA circuits are inherently prone to faults due to variations in manufacturing processes and due to the influence of environmental factors. These faults degrade the performance of a QCA circuit considerably. Hence, fault tolerance is one of the major factors of consideration while designing a QCA circuit, particularly when the application requires very reliable and continuous operation, say in an IoT system. As such, this work presents a fault tolerant Carry Skip Adder (CSA) for QCA-based circuits. The fault tolerance of basic arithmetic components of IoT nodes performing tasks corresponding to the signal processing, control, and data manipulations is enhanced in the proposed architecture. The area occupied by a fault-tolerant full-adder circuit is 0.06 μm² and a clock cycle is 0.75; its core will be used in the CSA design. It realizes fault-tolerant multiplexers (MUX) and a majority gate, which gives the same result when there is a missing or extra single-cell fault. The most astonishing characteristic of this transistor-based CSA is its 85% tolerance for different types of failures. The CSA with three layers contains 1542 quantum cells, 4.75 clock phases, and occupies an area of 4.59 μm². It is compact and efficient architecture; therefore, it is very suitable for IoT applications where the area constraint and power efficiency are the key issues. The proposed CSA will increase the robustness and reliability of QCA-based digital circuits by integrating fault tolerance into its design such that the circuitry based on QCA can keep their functionality on even in fault-prone environments.